Physiology of sport and exercise - Kennedy, Larry W., ....-; Costill, David L., ....-; Wilmore, Jack H., 1938-2014 (Champaign : Human Kinetics, 2015)
The Sixth Edition of this international bestseller frames research findings in physiology in a reader-friendly format, making this textbook a favourite of lecturers and students alike. It offers a simple way for students to develop an understanding of the body's abilities to perform various types and intensities of exercise and sport, to adapt to stressful situations and to improve its physiological capacities. Students and instructors can take advantage of the web-based ancillaries that accompany the text and include new animations, videos and audio clips. Physiology of Sport and Exercise has been a cornerstone textbook of the engaging field of exercise physiology. Through dynamic and interactive learning activities, easy-to-follow layouts, and research-oriented content, students and instructors will find this an invaluable resource for their continued education.
Keywords: Fysiologie